Tainted Executives as Outside Directors - Baer, Leah M.; Ertimur, Yonca; Zhang, Jingjing (The Accounting Review, 2023)
ABSTRACT We examine outside board appointments of executives allegedly involved in governance failures—“tainted” executives—to shed light on appointing firms’ underlying motivations. Less attractive firms and those with greater advising needs are more likely to appoint tainted executives to their boards than other firms are. Tainted appointees are less likely to be placed on the nominating and governance committees than nontainted appointees. Tainted appointees have similar or better skill sets compared with nontainted appointees. Firms that appoint tainted executives to their boards display an improvement in operating performance in the postappointment period relative to the preappointment period and relative to a matched control sample. We do not find evidence of poor monitoring outcomes for these firms. Overall, our evidence suggests that board needs, not a conspicuous attempt to weaken monitoring, drive the appointment of tainted executives to boards. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G34; K22; M41.